Clinical Results of Diffractive, Refractive, Hybrid Multifocal, and Monofocal Intraocular Lenses - Agnieszka Dyrda; Ana Martínez-Palmer; Daniel Martín-Moral; Amanda Rey; Antonio Morilla; Miguel Castilla-Martí; Janny Aronés-Santivañez (Journal of Ophthalmology)
Purpose. To present the outcomes of hybrid multifocal and monofocal intraocular lenses (IOLs) and to compare with refractive and diffractive multifocal IOLs (MFIOLs). Methods. Three hundred twenty eyes (160 patients) underwent cataract surgery with randomized IOLs bilateral implantation. Changes in uncorrected and distance-corrected logMAR distance, intermediate and near (UNVA and DCNVA) visual acuity (VA), contrast sensitivity (CS), presence of dysphotopsia, spectacle independence, and patient satisfaction were analyzed. Results. Postoperative VA in the hybrid (OptiVis) group was improved in all distances (p<0.001). OptiVis acted superiorly to monofocal IOLs in UNVA and DCNVA (p<0.001 for both) and to refractive ones in DCNVA (p<0.005). Distance, mesopic, without glare CS in OptiVis was lower than in the monofocal group and similar to other MFIOLs. No differences in dysphotopsia pre- and postoperatively and spectacle independence in near for OptiVis and refractive MFIOLs were detected. OptiVis patients were more satisfied than those with monofocal IOLs (p=0.015). Conclusions. After cataract surgery, patients with OptiVis improved VA in all distances. Near and intermediate VA was better than monofocal, and DCNVA was better than the refractive group. CS was lower in OptiVis than in the monofocal group, but there was no difference between MFIOLs. Patient satisfaction was higher in OptiVis than in the monofocal group. This trial is registered with NCT03512626.